Uji Efektifitas Rebusan Dan Infused Kapulaga (Ammonum compactum) Terhadap Pertumbuhan Bakteri Enterotoxigenic Escherichia coli - Susmayanti, Novi (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2021)
Cardamom (Amomum compactum) is a native Indonesian rhizome which is widely used by several people and has many benefits. Cardamom contains alkaloid chemicals, saponins, tannins, polyphenols, and flavonoids which act as antibacterials. Escherichia coli is a Gram negative bacteria and can be pathogenic for a person. This study aims to analyze the minimum concentration of boiled and infused cardamom (Amomum compactum) in preventing the growth of Enterotoxigenic Escherichia coli. This type of research is a laboratory experiment with an antibacterial test with the disc diffusion method. The results of this study are that decoction and infused cardamom (Amomum compactum) can inhibit the growth of the microbial Enterotoxigenic Escherichia coli (ETEC). Cardamom decoction at a concentration of 90 and 100% was able to inhibit the growth of strong bacteria. Infused cardamom at a concentration of 80%, 90% and 100% is able to inhibit the growth of bacteria with strong categoriesÂ Keywords : cardamom (Amomum compactum), infused, enterotoxigenic Escherichia coli (ETEC)